Sea Ice Motion in Response to Surface Wind and Ocean Current in the Southern Ocean - KIMURA, Noriaki (Journal of the Meteorological Society of Japan, 2004)
Using satellite-derived daily sea ice motion, this paper presents maps showing the relationship between the ice motion and surface wind, and mean ocean current in the Southern Ocean. The daily ice motions were derived from Defense Meteorological Satellite Program (DMSP) Special Sensor Microwave Imager (SSM/I) images. The mean ice motion field is characterized by eastward circumpolar drift; northward drifts in the Weddell Sea, Ross Sea, and areas around 80°E; and narrow westward coastal currents. A linear formula is used to examine the relationship between the ice motion and wind. It was found that daily variation in the ice motion is closely correlated with wind speed fluctuation, and that features of mean ice motion are mainly attributable to atmospheric forcing. The speed reduction factor (ratio of ice speed to wind speed) is relatively small near the coast, and increases with distance from the coast. Surface ocean currents beneath the ice cover were derived by subtracting the wind effect from the ice motion. It is revealed that the ocean current field is associated with the bottom topography.